2020
DOI: 10.1101/2020.04.14.20055038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First time genotyping of Cryptosporidium spp. isolates from diarrheic stools of Algerian HIV-Infected subjects supports predominant zoonotic transmission routes

Abstract: Background Cryptosporidium is a significant cause of chronic diarrhoea and death in HIV-infected patients. Although HIV-infected patients under HAART have currently reduced risk of suffering from opportunistic infections, opportunistic gastrointestinal infections such as cryptosporidiosis still occur. Currently, there are no data on genetic characteristics of Cryptosporidium isolates from cryptosporidiosis patients in Algeria. This study was aimed at identifying Cryptosporidium species and subtype families pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…The Ib subtype family of C. hominis is wide spread and that may cause infection in human and animals especially sheep. This agrees with [46,47] who revealed that animals may be considered as a source for C. hominis.…”
Section: Discussionsupporting
confidence: 91%
“…The Ib subtype family of C. hominis is wide spread and that may cause infection in human and animals especially sheep. This agrees with [46,47] who revealed that animals may be considered as a source for C. hominis.…”
Section: Discussionsupporting
confidence: 91%